Development and Content Validation of a HOTS-Oriented Performance Assessment for Physics Practicum in Higher Education to Support SDG 4 - Emiliannur; Fuja Novitra; Rahma Doni; Metta Liana; Nanang Winarno; Lukman Hakim (Postgraduate, University of Mataram, 2026)
Higher education is expected to equip students with Higher Order Thinking Skills (HOTS); however, assessment practices in physics laboratory learning still often emphasize procedural performance. This study aims to analyze assessment needs and to develop and conduct content validation of a HOTS-oriented performance assessment for physics laboratory learning in higher education to support Sustainable Development Goal 4 (Quality Education). This study employed a research and development (R&D) approach using the ADDIE model, limited to the Analyze, Design, and Develop stages. The participants were 49 undergraduate physics students selected using purposive sampling and laboratory assistants involved in practicum activities. Data were collected through essay tests, practicum module analysis, interviews, and observations, and analyzed using descriptive quantitative and qualitative methods. Content validity was evaluated through expert judgment using Aiken’s V index. The results showed that existing assessments had not optimally measured HOTS, particularly evaluating (C5) and creating (C6). Therefore, a HOTS-oriented performance assessment integrating C4, C5, and C6 was developed, consisting of performance tasks, scoring rubrics, observation sheets, and self- and peer-assessment instruments. The content validation results indicated high validity with an Aiken’s V value of 0.89. These findings provide a validated conceptual foundation for further implementation and evaluation to support SDG 4 in higher education.